The Effect of Generative Learning Model to the Creative Thinking Skills of High School Students - Kemara, Nabila Indah (Physics Learning and Education, 2025)
The purpose of this research is to determine the effectiveness of generative learning model to the creative thinking skills of the high school students. The problem is the creative thinking skills of students are still low. The type of this research is a quasi experiment with cluster sampling technique. Creative thinking skills is measured by adapting torrance test of creative thinking. Before using the instrument, it has to be validated by physics expert. The validity score is 0.93 and is categorized valid. The instrument is also tested for its validity and reliskill. The data is obtained from the creative thinking skills of students which is adopting torrance test of creative thinking. Data analysis is done by using t-test statistic. The result of this research shows that the creative thinking skills of students in experimental class is 82 and the creative thinking skills of students in control class is 75. Based on the table of t-distribution, ttable is 1,99 and tcount is 2,78. The requirement of H0 is denied is when . The score of tcount is in H0 denial, so H1 is accepted which means that there is an effect of generative learning model towards the creative thinking skills of students.